Stunting Prevention Intervention in Tungkaran Village with Improved Sanitation "Healthy Latrines" Pelaihari District, Tanah Laut - Annisa Annisa (Borneo Community Development, 2024)
Stunting in 1,000 HPK infants and children is currently a major problem in South Kalimantan, one of which is in Tanah Laut District. One of the risk factors for Stunting is poor environmental sanitation. Pelaihari sub-district one of the locus of Stunting in Tanah Laut Regency so that it becomes one the district government's priority in efforts to reduce and prevent Stunting. Healthy latrines it is a family sanitation facility that must be owned by every household. The purpose of this activity is to educate and increase public awareness about healthy latrines connecting the needs of the community for healthy latrines with the incidence of Stunting children in one of the villages in Pelaihari district, namely Tungkaran Village. The method used in this community service activity is to educate directly about healthy latrines from house to house targets that fall into the category of less decent latrine ownership, as well as to village officials, community leaders and the community in Tungkaran Village, Pelaihari District. Educational activities resulted in mutual agreement that it is important to have household healthy latrines in order to maintain health by making the living environment clean and healthy.